2018
DOI: 10.1128/jvi.00858-17
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Influenza A Virus M1 Protein Enhance Virus Budding To Complement Lethal Mutations in the M2 Cytoplasmic Tail

Abstract: The influenza A virus M1 and M2 proteins play important roles in virus assembly and in the morphology of virus particles. Mutations in the distal cytoplasmic tail region of M2, and in particular a tyrosine-to-alanine mutation at residue 76 (Y76A), were essential for infectious virus production and filament formation while having limited effects on total virus particle budding. Using a novel selection method, mutations at seven different M1 amino acids (residue 73, 94, 135, 136, or 138 or a double mutation, 93/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…There are other mutations in M2 apart from residue 78 in recent H1N1 isolates. A recent study indicated that a lethal mutation in the M2 cytoplasmic tail can be compensated for by mutations in the M1 protein to restore the production of infectious virus (34). Together, the K78 mutation plus other mutations may affect virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…There are other mutations in M2 apart from residue 78 in recent H1N1 isolates. A recent study indicated that a lethal mutation in the M2 cytoplasmic tail can be compensated for by mutations in the M1 protein to restore the production of infectious virus (34). Together, the K78 mutation plus other mutations may affect virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…RNA from virus particles secreted into the supernatant was isolated and reverse transcribed into cDNA as described previously (78). Virus supernatant from high-MOI infections was concentrated through a 35% sucrose cushion at 118,000 ϫ g for 1 h in an Optima Max-TL Beckman Ultracentrifuge.…”
Section: Methodsmentioning
confidence: 99%
“…Virus supernatant from high-MOI infections was concentrated through a 35% sucrose cushion at 118,000 ϫ g for 1 h in an Optima Max-TL Beckman Ultracentrifuge. The qPCR assay was performed as described previously (78), except the sample volumes and primers described above were used. All samples were mixed with 4ϫ SDS-PAGE sample buffer containing dithiothreitol (DTT; ThermoFisher) before heating for 5 min at 100°C.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, MDM showed very few buds on their surface (Figure 4), suggesting that in MDM, an earlier role for M2 in virus particle assembly is more prominent than in epithelial cells. Consistent with this early role of M2 in IAV assembly, M2 functions in recruitment of M1 and vRNP to assembly sites (41, 5863), which is important for initiation of IAV particle assembly or elongation of filamentous particles (58, 60, 6571). A defect in incorporation of M1 and/or vRNP into budding virus particles due to the failure of M2 recruitment may also explain the reduction in infectivity per particle observed for MDM-derived virus relative to dTHP1-derived virus (Figure 2B).…”
Section: Discussionmentioning
confidence: 64%